Studying on Chemical Properties of Paddy Soil In Sunggal Sub District Deli Serdang Regency - Yunita Carolin Hutapea; Abdul Rauf; Mukhlis Mukhlis (Jurnal Agroekoteknologi, 2018)
This study aimed to analyze and determine the chemical properties of paddy soil in the Sunggal sub district so that it can be determined Sunggal paddy soil fertilizer recommendations. Research using surveys with sampling techniques stratified random sampling based on the type of rice fields Rainfed and Irrigation and data analysis pH with methods Elektrometri, C organic method of Walkley and Black, the N total with methods Kjeldhal, P available by the method of Bray II, cations base (K+,Na+,Ca2+,Mg2+)by the method of extraction of NH4OAc 1N pH 7, CEC with NH4OAc 1 N pH 7 extraction method and Base Saturation with the calculations. Results of research on the soil for rainfed and irrigation showed that the pH of dominant soil slightly acid, organic C dominant low, N total is low, P available predominantly very low, K exchange dominant low, Ca exchange is low, Mg exchange the dominant medium, Na exchange low dominant, dominant CEC being, Base Saturation is very low dominant. Soil fertility status of rainfed and irrigation is relatively very low to low, except in rainfed Puji Mulyo village were moderate due to high organic C.